PEMANFAATAN LIMBAH RAMBUT JAGUNG (Zea mays L.) SEBAGAI MINUMAN HERBAL DI DESA NANGA TAMAN KECAMATAN NANGA TAMAN KABUPATEN SEKADAU - Tuti Kurniati; Raudhatul Fadhilah (Jurnal Buletin Al-Ribaath, 2017)
Nanga Taman Village whose field was about 415 ha and produce 828 tons of corn ears annually is potential natural resource of corn in Kalimantan Barat. As only its kernel has been used before, the other parts became a waste, which is threatening surrounding environment. The corn silk was unused part of the corn which can be converted into herbal tea for keeping body healthy and cure several disease. However, the villager did not have basic knowledge and skill to utilize it. To improve their knowledge, a training course was given as part of community service in Nanga Taman Village. By having this activity, participants’ attitude toward corn silk were improved as well as it offered a solution to reduce their garbage. Keywords: Nanga Taman Village, herbal tea, corn silk